2012
DOI: 10.1038/nrneurol.2012.27
|View full text |Cite
|
Sign up to set email alerts
|

Modifiable factors that alter the size of the hippocampus with ageing

Abstract: The hippocampus is particularly vulnerable to the neurotoxic effects of obesity, diabetes mellitus, hypertension, hypoxic brain injury, obstructive sleep apnoea, bipolar disorder, clinical depression and head trauma. Patients with these conditions often have smaller hippocampi and experience a greater degree of cognitive decline than individuals without these comorbidities. Moreover, hippocampal atrophy is an established indicator for conversion from the normal ageing process to developing mild cognitive impai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
206
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 297 publications
(222 citation statements)
references
References 163 publications
6
206
0
2
Order By: Relevance
“…Investigations into structural brain changes has largely confirmed that obese and overweight individuals have a smaller hippocampal size compared to healthy individuals (Fotuhi et al, 2012, Mueller et al, 2012, Raji et al, 2010, Taki et al, 2008. A higher mid-life BMI also increases the rate of hippocampal atrophy in late life (Jagust et al, 2005, Taki et al, 2008.…”
Section: How Obesity Influences Biological Pathways Associated With Pmentioning
confidence: 93%
“…Investigations into structural brain changes has largely confirmed that obese and overweight individuals have a smaller hippocampal size compared to healthy individuals (Fotuhi et al, 2012, Mueller et al, 2012, Raji et al, 2010, Taki et al, 2008. A higher mid-life BMI also increases the rate of hippocampal atrophy in late life (Jagust et al, 2005, Taki et al, 2008.…”
Section: How Obesity Influences Biological Pathways Associated With Pmentioning
confidence: 93%
“…The high hippocampal involvement may be related to its high vulnerability to the neurotoxic effects of osmotic derangements 49 and systemic stresses in general. 50,51 In reviewed cases, contrast enhancement associated with ODS lesions was reported in 1 patient, 23 which has also been reported in some cases of hyponatremia. 52 Although inconsistently found, contrast enhancement is in agreement with the pathophysiologic changes observed in experimental models of ODS, in which BBB disruption occurs secondary to osmotic stress and is thought to be one of the leading factors in pathogenesis of ODS.…”
Section: Osmotic Demyelination Syndromementioning
confidence: 99%
“…78 Of note, WM is particularly vulnerable to the inflammatory neurotoxic Diffusion tensor imaging in BD effects of BD. 79 The cognitive decline that occurs over the course of the disease seems to be associated, at least in part, with vulnerability to the toxic effects of inflammation. 79 Additionally, immune disturbances have been linked to BD and symptom severity, mood episodes, staging, effect of medications, metabolic disturbances, neurotrophin alterations, and increased frequency of comorbid autoimmune and allergic disorders.…”
Section: Continued On Next Pagementioning
confidence: 99%
“…79 The cognitive decline that occurs over the course of the disease seems to be associated, at least in part, with vulnerability to the toxic effects of inflammation. 79 Additionally, immune disturbances have been linked to BD and symptom severity, mood episodes, staging, effect of medications, metabolic disturbances, neurotrophin alterations, and increased frequency of comorbid autoimmune and allergic disorders. 80 In this context, DTI findings could provide a better understanding of the neurobiological underpinnings of pathophysiology in BD.…”
Section: Continued On Next Pagementioning
confidence: 99%